Genetic epidemiology of Plasmid Mediated Class C Beta-Lactamase among Enterobacteriaceae isolates - Chuong Van Le; Nguyen Nhat Tran; Phuong Thi Be Nguyen; Nga Thi Le; Duong Thuy Le (Revista Cubana de Medicina Militar)
Introduction: Plasmid-mediated class C ß-lactamase (pAmpC) is a member of broad-spectrum ß-lactamase that spreads worldwide. However, its prevalence was under-evaluated. Objective: To characterize the prevalence and distribution of pAmpC types in 294 cefoxitin (FOX) and third-generation cephalosporin (3GC) resistant Enterobacteriaceae collected in several regions of Thailand and Vietnam in 2018 and 2020. Methods: Multiplex Polymerase Chain Reaction (PCR) for pAmpC identification was utilized to investigate prevalence and diversification of pAmpC among 294 cefoxitin and third-generation cephalosporin resistant Enterobacteriaceae isolated from Thailand (n= 197) and Vietnam (n= 97). Results: The prevalence of pAmpC was 37.1 % found in second and third-generation cephalosporin resistant Enterobacteriaceae. CMY-2 like was prominent in Thailand and Vietnam; however, prevalence of CMY-2 was varied in each hospital. DHA contributed 25.7 %, ACT/MIR rate was dominant in Chiang Rai hospital, reached 100 % in Thanh Hoa Pediatrics hospital. Worrisome, 3.7 % - isolates carried two types of pAmpC. The incidence of pAmpC in Vietnam was significantly higher than those in Thailand. Conclusions: These findings provide evidence-based of highly spreading and diversified distribution of transferable AmpC among Enterobacteriaceae in two Asia-Pacific countries.